Proceedings of the 2004 ACM Conference on Computer Supported Cooperative Work 2004
DOI: 10.1145/1031607.1031649
|View full text |Cite
|
Sign up to set email alerts
|

Toward universal mobile interaction for shared displays

Abstract: Researchers have noted conflicting trends in collaboration technologies between delivering more information on larger displays and exploiting mobility on smaller devices. Large, shared displays provide greater choice in the presentation of information, but mobile devices offer greater flexibility in the access of information. We describe a platform that leverages the best of both worlds by allowing multiple users to access and interact with a large, shared display using their own personal mobile devices, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 9 publications
0
39
0
Order By: Relevance
“…It consists of separate gateways for each interaction method and allows several user interfaces to be used in parallel [14]. Paek et al suggested I/O modules for using different techniques simultaneously, providing a similar solution [28]. To support parallel interaction, tunneling interaction via a server has been explored [19,31].…”
Section: Related Workmentioning
confidence: 99%
“…It consists of separate gateways for each interaction method and allows several user interfaces to be used in parallel [14]. Paek et al suggested I/O modules for using different techniques simultaneously, providing a similar solution [28]. To support parallel interaction, tunneling interaction via a server has been explored [19,31].…”
Section: Related Workmentioning
confidence: 99%
“…Paek et al [15] has identified that as an incentive, a lottery could notify random participants that they have won a prize. Our test users agreed: "I think the idea of having a lottery to win a pizza or a beer in such a system is good" (13/0).…”
Section: Enticing Interaction With Public Displaymentioning
confidence: 99%
“…Personal mobile phones, on the other hand, disperse control and access to participating users, though limited conceptual power and smaller screen sizes often hinder dynamic interaction. Thus, connecting shared displays to personal mobile phones is an obvious way to leverage the best of both worlds [15].…”
Section: Introductionmentioning
confidence: 99%
“…Architectures for mobile interaction with shared displays [16] and multi-cursor interaction [1] illustrate the complexity when designing multi-display groupware environments. Tse et al [22] describe a set of experiments where shared workspaces were partitioned by participants into individual areas to address interference, while one of the motivations for designing cooperative gestures [12] was to clarify users' intentions.…”
Section: Figmentioning
confidence: 99%
“…We have therefore developed a set of tools and techniques, focusing on multi-display groupware (MDG), as shown in Figure 1. In the spirit of previous work [1,13,16,19,21], our goal has been to distribute the interactive capabilities at such meetings among participants. While our work is applied to the medical domain, we also find it generally applicable to other types of MDG and single-display groupware (SDG) scenarios [21,13,23].…”
Section: Introductionmentioning
confidence: 99%